A new species of Polynoncus Burmeister, 1876 from Brazil (Coleoptera: Trogidae) - Huchet, Jean-Bernard; Costa-Silva, Vinicius Da (Zootaxa, 2018)
Polynoncus vazdemelloi Huchet & Costa-Silva new species (Coleoptera: Trogidae) from Brazil is described and illustrated with data about the natural history and geographic distribution. Comparative data between P. vazdemelloi, P. juglans (Ratcliffe, 1978), and P. gemmingeri (Harold, 1872), species closely related morphologically, are given. Omorgus (Omorgus) triestinae Pittino, 1987 is removed from synonymy with O. (O.) suberosus (Fabricius, 1775) and reinstated as a valid species.